La socialización profesional del entrenador deportivo como un proceso de formación en la adquisición de conocimientos - Rodrigues, Heitor De Andrade; Paes, Roberto Rodrigues; Neto, Samuel De Souza [UNESP] (My University, 2016)
The purpose of the research was to investigate the process of professional socialization of youth basketball coaches, in order to identify the knowledge acquired throughout time and analyze the nature of the formation processes behind the appropriation of knowledge. It was chosen a quantitative research, with the narrative interview, ethno-sociological perspective, to collect technical data. Thirteen coaches were chosen for the research. The results revealed the appropriation of a diverse set of knowledge (experiential, academic and professional), the product of successive socialization, supported by artisanal education, academic-scientific background and reflective practice.
A socialização profissional do treinador esportivo como um processo formativo de aquisição de saberes
Professional socialization of the sport coach as a formative process of knowledge acquiring
Keywords: Coaches; Knowledge; Socialization